Ionomers Modify the Selectivity of Cu‐Catalyzed Electrochemical CO2 Reduction. Issue 5 (11th January 2023) - Chang, Miyeon; Ren, Wenhao; Ni, Weiyan; Lee, Seunghwa; Hu, Xile
Abstract: Electrochemical reduction of carbon dioxide (CO2 RR) to produce energy‐rich fuels using copper‐based electrocatalysts is widely studied as a possible solution to CO2 recycling. Ionomers are commonly used as binders to prepare catalyst‐loaded electrodes, but their effects on the performance have not been fully investigated. In this study, electrochemical and operando Raman spectroscopic measurements are used to study the effects of three archetypical ionomers [Nafion, Sustainion‐type XA‐9, and poly(terphenyl piperidinium) (PTP)] on Cu‐catalyzed CO2 reduction at high current densities (up to 200 mA cm −2 ). Nafion is found to have little influence, whereas XA‐9 promotes the formation of CO over multicarbon products and PTP favors hydrogen and formate production. Charge and hydrophobicity/hydrophilicity are found to be important parameters of the ionomers. The observed effects are attributed to the charge transfer between Cu and XA‐9 weakening the CO adsorption energy, whereas the hydrophilicity of PTP reduces M−H energy. This study reveals the structure‐sensitive nature of the ionomer‐catalyst interaction in CO2 RR. Abstract : Bound to change : Ionomers, such as Nafion, XA‐9, and poly(terphenyl piperidinium) (PTP), are commonly used as binders to prepare catalyst‐loaded electrodes for the electrochemical reduction of carbon dioxide (CO2 RR). However, these ionomers alter the selectivity of the CO2 RR on Cu at high current densities. Their effects depend on the charge and hydrophobicity/hydrophilicity of the ionomers.